Development of the Tactical Human Optimization, Rapid Rehabilitation, and Reconditioning Program Military Operator Readiness Assessment for the Special Forces Operator. Issue 6 (December 2016) - Bear, Ray; Sanders, Mike; Pompili, Jason; Stucky, Lance; Walters, Andrew; Simmons, Jerry; Lacanilao, Paul; Eagle, Shawn; Grier, Tyson; DeGroot, MAJ David; Lovalekar, Mita T.; Nindl, Bradley C.; et al.
Abstract : ABSTRACT: THE AIM OF THIS ARTICLE IS TO DESCRIBE A NOVEL MILITARY UNIQUE OPERATOR READINESS ASSESSMENT (ORA). THE ORA WAS DESIGNED BY TACTICAL HUMAN OPTIMIZATION, RAPID REHABILITATION, AND RECONDITIONING PROFESSIONALS AS PART OF A RETURN-TO-DUTY PROTOCOL TO SPECIFICALLY EVALUATE THE MUSCULOSKELETAL READINESS AND PHYSIOLOGICAL PREPAREDNESS OF PREVIOUSLY INJURED OPERATORS. THE ORA COMPRISES 11 TACTICALLY RELEVANT AND PHYSICALLY TAXING EVENTS COMPLETED IN ORDER WITH A 2-MINUTE REST BETWEEN EVENTS. DEVELOPMENT OF A COMPREHENSIVE RETURN-TO-DUTY PROTOCOL OF THIS NATURE IS A NECESSARY FIRST STEP FOR TACTICAL STRENGTH COACHES TO REDUCE RISK OF REINJURY TO PREVIOUSLY INJURED PERSONNEL.